To determine which of the options results in the answer of 1, let's evaluate each one:
-
(-2.97) to the power of 0: Any non-zero number raised to the power of 0 is equal to 1. Therefore, \((-2.97)^0 = 1\).
-
5 to the power of 0 + 9 to the power of 0: Both \(5^0\) and \(9^0\) equal 1. Thus, \(5^0 + 9^0 = 1 + 1 = 2\).
-
13 - (7.42)^0: \( (7.42)^0 = 1\), so \(13 - (7.42)^0 = 13 - 1 = 12\).
-
3 (8^0): \( (8^0) = 1\), so \(3 \times (8^0) = 3 \times 1 = 3\).
Now, summarizing the results:
- (-2.97)^0 = 1
- 5^0 + 9^0 = 2
- 13 - (7.42)^0 = 12
- 3 (8^0) = 3
Thus, the only expression that results in the answer of 1 is (-2.97) to the power of 0.